Public perception of hospital-based nursing care: a study of the Tamale Metropolis in Ghana - Agyei, Kofi G.; Agambire, Ramatu; Ansong, Cecilia A.; Tano, Priscilla F.; Mohammed, Rumana Saeed; Azumah, Fawzia; Yoobe, Roger Z. (International Journal Of Community Medicine And Public Health, 2023)
Background: A key contributor for the improvement of patients’ health outcomes and their holistic well-being after hospital stay is the quality of nursing care received in hospitals of which may also be influenced by the perceptions the public precisely patients have about nursing care. This study assessed the public perception of hospital-based nursing care in the Tamale metropolis. Methods: The study was conducted at the Tamale Central Hospital in Ghana and employed a qualitative approach with an in-depth interview guide in collecting primary data from 30 participants. The interviews were transcribed and analysed using thematic analysis and the common themes identified were presented in line with the objectives of the study. Results: With respect to the experiences the patients had, it was revealed that they had both negative and positive experiences. While the positive experiences were related to the quality of care, the negative experiences on the other hand were on the attitude of nurses. The study also revealed that nurses’ attitudes, mode of service delivery and professional ethics which include respect for patient and communication were the major factors that influence patients’ satisfaction. Conclusions: The study revealed that the public have negative perception towards nursing care resulting from unmet expectations. Policies should be formulated to ensure effective communication, empathy, and respect which will help ensure patients satisfaction with healthcare delivery at the hospitals since these appear to be the best predictors of patients’ satisfaction.